Emergence in the WAEMU and EMCCA areas - Ntwali, Valéry IRAGI; Centwali, Guillain CIRHUZA (Studia Universitatis Babeș-Bolyai Studia Europaea, 2021)
The Economic and Monetary Community of Central Africa (EMCCA) and the West African Economic and Monetary Union (WAEMU) have succeeded in stabilizing their monetary systems, but this monetary stability has not been accompanied by real emergence. The economies of most of the member states of these two organizations are based on commodities and cocoa, which means that they are completely volatile and therefore lack the stability necessary for real emergence. This study based mainly on documentary research through the exploitation of reports produced by various international and regional institutions such as the IMF, the World Bank, the African Development Bank, ECOWAS, etc., and the writings of various emergence theorists, shows the role that industrialization and diversification of the economies of the WAEMU and EMCCA zones should play in the development of the economies of the member states and the improvement of the living conditions of the populations.
Keywords: CEMAC; Emergence; Spaces; UEMOA; WAEMU

The Impact of Covid-19 Pandemic on Women In Nigeria - Iheanacho-Shahid, Jennifer (African Journal of Politics and Administrative Studies, 2021)
The paper examines the impact of corona-virus pandemic on women in Nigeria. Emergencies and times of unrest have been linked with increasing reports of Gender Based Violence. Pandemics and Epidemics on the other hand are no exception. The COVID-19 pandemic has been associated with an increase in Gender Based Violence termed the Shadow Pandemic due to the control measures adopted in containing the spread of the virus. The paper adopted the Social Ecological Model to explain and understand the factors that contribute to the increase of Gender Based Violence against women during emergencies or natural disasters and how interaction of individual and environmental factors influence behavior and attitudes that create an atmosphere that encourages violence. The paper was based on secondary sources of data.  The findings of the paper revealed that the lockdown isolated women and attenuated opportunities for them to divulge the abuse or receive necessary support services or resources.  The paper also discovered that there has been an increased rate of reported cases of Gender Based Violence during the months of lockdown in Nigeria. The paper concluded that the corona-virus outbreak has exposed the shadow pandemic of violence and inequality and the exclusion of the Minister of Women Affairs and Social Development is a step in the wrong direction . The paper recommended that it is pertinent to integrate gender lens into disease response and protection mechanism and Gender Based Violence services should be termed as essential duties during crisis and emergencies.

Story of a legal codex(t) : writing law in code - Ma, Megan (Institut d'études politiques, 2021)
How is the law measured? For long, it appeared that the law cannot be measured. While there are standards and processes, the law was not regarded as quantifiable. Only in the advent of recent technological advancements in law have there been considerations for metrics. These technologies sought to tackle the legal field’s inherent protectionism fueled by deep asymmetries in information. Consequently, the rise in legal ‘metrics’ stems from an access to justice perspective. The assumption is that in making the law more quantifiable, knowledge that has been historically opaque and inaccessible outside of the legal community may be revealed.Alternatively, it may be argued that the law has always been measurable. Words, through linguistic devices, have shaped legal meaning. In effect, the law conceivably has been measured by its words. In fact, “law exists as text” (Hildebrandt, 2015). I further this line of thinking by investigating natural language as the key vessel through which the law has manifested itself. Does the law depend on natural language to do its work? Importantly, is the language sufficient at housing legal norms?This dissertation seeks to tell a narrative. Broadly, it chronicles the story of law’s intimate relationship with language. But more specifically, the thesis details the law’s recent encounter with the digital. When law met technology, its relationship with language changed, invoking skepticism around its fitness for the conveyance of legal concepts. With the introduction of an innovative player – code – the law had perceivably found its new linguistic match. As a result, code was tested for its ability to perform and accommodate for the law’s demands. Ultimately, confronted by natural language and code, the law is asked whether code can be its language. Comment mesure-t-on le droit ? Longtemps, le droit semblait résister à la mesure. Bien qu'il existe des normes et des processus, le droit n'était pas considéré comme quantifiable. Ce n'est qu'avec l'avènement des récentes avancées technologiques dans le domaine du droit que l'on a commencé à envisager une telle quantification. Ces technologies ont cherché à s'attaquer au protectionnisme inhérent au domaine juridique, alimenté par de profondes asymétries d'information. Par conséquent, l'essor de la "métrique" juridique découle d'une perspective d'accès à la justice. L'hypothèse est qu'en rendant le droit plus quantifiable, des connaissances historiquement opaques et inaccessibles en dehors de la communauté juridique peuvent être révélées.On peut également faire valoir que le droit a toujours été mesurable. Les mots, par le biais de dispositifs linguistiques, ont façonné la signification juridique. En effet, il est concevable que le droit ait été mesuré par ses mots. En effet, "le droit existe en tant que texte" (Hildebrandt, 2015). J'approfondis cette ligne de pensée en examinant le langage naturel en tant que vecteur clé à travers lequel le droit s'est manifesté. La loi dépend-elle du langage naturel pour faire son travail ? Plus important encore, le langage est-il suffisant pour abriter les normes juridiques ?Cette thèse cherche à raconter une histoire. De manière générale, elle relate l'histoire de la relation intime du droit avec le langage. Mais plus spécifiquement, la thèse détaille la rencontre récente du droit avec le numérique. Lorsque le droit a rencontré la technologie, sa relation avec le langage a changé, suscitant le scepticisme quant à son aptitude à transmettre des concepts juridiques. Avec l'introduction d'un acteur innovant - le code - le droit a visiblement trouvé sa nouvelle adéquation linguistique. En conséquence, le code a été mis à l'épreuve quant à sa capacité à fonctionner et à répondre aux exigences du droit. Finalement, confronté au langage naturel et au code, le droit se demande si le code peut être son langage.
Keywords: Connaissance du contexte; Contextual knowledge; Droit et informatique; Informatique; Langage juridique (informatique); Langages de programmation; Law and computation; Linguistics; Linguistique; Programming languages

Four Essays on Tax Transition Reform in Developing Countries - Adandohoin, Kodjo (Université Clermont Auvergne, 2021)
Ces dernières années, la plupart des pays en développement sont confrontés à la nécessité de concilier deux impératifs : d’une part, une demande sociale forte qui nécessite un besoin de ressources publiques supplémentaires, et d’autre part le désarmement tarifaire consécutif aux politiques d’ouverture commerciale, qui les prive de la majeure partie de leurs recettes budgétaires. D’où l’impérieuse nécessité pour ces pays d’assurer une transition dans la structure de leur prélèvement public c’est à dire de transférer la pression fiscale du commerce extérieur vers la fiscalité domestique. Cette thèse s’intéresse à cette problématique et vise à étudier les conditions de réussite d’un tel phénomène dans les pays en développement au travers de quatre essais empiriques. Le premier essai concerne le rôle de la TVA et des droits d’accises dans une première vague de transition. La TVA étant un impôt neutre et à très large assiette fiscale, cette dernière a été suggérée comme outil majeur pour réussir le transfert des ressources publiques du cordon douanier vers la fiscalité domestique et en complémentarité avec les droits d’accises. Nos investigations empiriques soutiennent cette assertion théorique et montrent que le couple TVA-accise joue bien ce rôle de substitut aux recettes de porte en quasi baisse suite au démantèlement tarifaire dans les pays. Néanmoins le rôle d’appui de la TVA et des droits d’accises est limité à partir d’un certain seuil de baisse des recettes de porte, qui traduit aussi le fait que le potentiel de mobilisation fiscale par la TVA dans ces pays est limité et qu’il faudra s’en préoccuper. Dans le second essai nous analysons la transition de seconde génération basée sur les impôts directs (impôts sur les revenus et impôts fonciers). Nous trouvons que les impôts directs sont des outils pauvres de transition fiscale dans les pays en développement. Pourtant, nous trouvons que le développement financier est un médiateur certain et incontestable à une politique de transition fiscale de seconde génération basée sur les impôts directs, car permettant de recouper l’information sur les revenus des contribuables et de générer des traces documentaires à l’administration fiscale, qui permettent d’envisager une mise à fiscalisation des contribuables, gage de recettes fiscales directes supplémentaires dans les pays. Dans le troisième essai, nous nous intéressons à l’effet de la mise en place d’une réforme de transition fiscale sur l’efficience dans la collecte des recettes en menant une étude de cas pour l’union économique et monétaire ouest africaine (UEMOA). Nos résultats supportent l’affirmative, en ce sens que la réforme accroit globalement une mobilisation efficiente des recettes dans la zone UEMOA. Cette efficience entrainerait par ailleurs avec elle une amélioration du climat des affaires dans la zone, suite à la mise en place de cette réforme. Enfin nous terminons cette thèse par un quatrième essai qui interroge quand à lui les impacts distributifs et de pauvreté d’une réforme de transition fiscale basée sur la TVA. Quoique les résultats montrent une incidence régressive de la réforme sur le revenu des ménages, une redistribution par la dépense aurait le mérite d’atténuer l’incidence sociale de cette stratégie de réforme sur le revenu des contribuables.
Keywords: 2SLS-IV model; Accises; Administration fiscale; Analyse des frontières stochastiques; Business climate; Climat des affaires; Computable general equilibrium; Contrôle Synthétique; Coordination fiscale; Corporate tax; Developing countries; Développement financier; Efficience; Efficiency; Effort fiscal; Excise; Exemptions; Exonérations; Financial development; Fiscalité; GMM; Harmonisation; Harmonization; Impôt foncier; Impôt sur le revenu; Impôt sur les sociétés; Income tax; Inequality; Internet; Inégalités; Micro-simulation; Modèle 2SLS-IV; Pauvreté; Pays en développement; Politique fiscale -- Pays en voie de développement; Potentiel fiscal; Poverty; Probit and Logit; Probit et Logit; Propensity scores; Property tax; Réforme fiscale; Scores de Propension; Stochastic frontier analysis; Synthetic control; TVA; Tax administration; Tax coordination; Tax effort; Tax potential; Tax reform; Tax transition; Taxation; Taxes sur le commerce extérieur; Trade taxes; Transition fiscale; VAT; Équilibre général calculable

Abuse of dominance and the Internet : an assessment of the South African Regulatory Framework - Koornhof, Pieter Gerhardus Jacobus (Stellenbosch University, 2021)
While electronic commerce in South Africa is still comparatively small, it is growing rapidly. The advent of the internet has potentially fundamental impacts on business and the law both locally and internationally. It is submitted the free competition on the internet is important and will continue to be so in the future. The research in this thesis relates to the rise of so-called internet monopolies (such as Google, Facebook and Amazon) and its implications for competition law enforcement. A particularly problematic aspect of the products provided by some of these companies is that their products and services are ostensibly free to consumers. This thesis examines whether the traditional model for the regulating abuse of dominance would be effective in the instance where such an internet monopoly is charged with a contravention under South African competition law. The research and analysis in the thesis are effectively divided into three parts. The first considers whether abuse of dominance related to the internet deserves closer analysis and also assesses the purposes of competition law and how these are changing (or should change) in the light of new technology and markets. The second part deals with abuse of dominance both generally and specifically in relation to the internet. In this context, the thesis considers how harms may manifest and how dominance may be determined in the context of the internet. The final part considers specific issues that may be problematic in light of the internet. The interrelationship between intellectual property and competition law is analysed, along with aspects pertaining to the assertion of jurisdiction, the nature of competition law enforcement and the extent to which different jurisdictions may (and/or should) cooperate in dealing with abuse of dominance on the internet. The thesis submits that the South African legislative framework for regulating abuse of dominance on the internet is broadly fit for purpose, but that there is a need for developing new approaches and policy within that framework. It contributes to the existing body of knowledge and discourse by providing a comprehensive overview of the regulatory framework in South Africa, informed by comparative analysis; by applying this in a new context (hitherto under-researched in the South African context), and by offering concrete suggestions to frame policy and approach.
Keywords: Competencia; Competition law; E-commerce; Electronic commerce; Internet monopolies; South African competition law; South African legislative Framework

Adoption des normes IFRS dans l’espace OHADA : Fondement théorique, intérêt et enjeux - Nyasseu, Emma Joachim; Yepdo, Florentin Gaël; Tatang Atabonfack, Pulchérie Léonie; Myskinole, Cheguem Shupo Davine (International Journal of Financial Accountability, Economics, Management, and Auditing, 2021)
Du fait des changements profonds qu’apportent les nouveaux concepts sur lesquels se base le référentiel de l’IASB, le passage aux normes IFRS a été qualifié d’une révolution comptable. Le but d’harmonisation de cette institution se réalise à travers la diffusion mondiale progressive des normes IFRS. Toutefois, les entreprises de la zone OHADA sont concernées par ce changement. Compte tenu de la rareté des travaux de recherche dans le domaine, nous essayons d’analyser à travers ce papier, l’adoption de telles normes en contexte OHADA. Pour y parvenir, cet article rappelle le mécanisme de passage aux normes IFRS dans l’espace OHADA, étudie ensuite l’intérêt pour les entreprises de cette zone et enfin met en évidence les enjeux liés à un tel projet. Les principaux résultats montrent que loin d’être un simple outil de présentation et de communication de l’information financière, les IFRS constituent pour les entreprises de la zone OHADA, un levier d’attraction des investisseurs et d’intégration économique.
Keywords: Normalisation comptable; Normes IFRS; OHADA; Référentiel; Révolution comptable

Botswana’s Anti-Money Laundering and Combating the Financing of Terrorism Regime - Tshiamo-Kgati, Kuda (University of Pretoria, 2021)
Money laundering, the financing of terrorism and proliferation financing continue to be serious threats to the stability of the international financial system. The international community therefore has prioritised the fight against these activities. For example, international bodies such as the Financial Action Task Force (FATF) and others have developed standards and recommendations against which countries and organisations are measured in this regard. Against this background, this thesis investigates to what extent Botswana’s legislative framework regarding money laundering, terrorism financing and other illicit financial flows complies with international standards, especially the FATF Recommendations. The study sets the scene by defining and describing money laundering, financing of terrorism and proliferation financing, after which the current statutory framework in Botswana is discussed in detail. After subsequently setting out the various global and regional (specifically African) initiatives in the fight against money laundering and other financial crimes, the current state of affairs in Botswana is benchmarked against both the South African framework as well as the FATF Recommendations. The investigation is limited to a technical assessment (doctrinal analysis) of Botswana law to determine the current compliance (or lack thereof) of the country’s statutory provisions and to make recommendations regarding how the framework can be improved. It is difficult for some countries, especially African countries like Botswana, to comply fully with the FATF Recommendations, since compliance can be expensive and dependent on high levels of expertise on the part of the relevant authorities. Therefore, such more vulnerable countries tend to face a higher risk of being used as conduits for money laundering and related activities. Despite these and other challenges, Botswana has gone to great lengths to re-assess and improve its anti-money laundering and combating the financing of terrorism (AML/CFT) legislation with a view to move towards full compliance with the FATF Recommendations. Nevertheless, the evaluation indicates that there are some remaining shortcomings in Botswana’s legislation. Consequently, the thesis concludes by proffering certain recommendations towards ensuring that Botswana’s AML/CFT legislation is rendered fully compliant with the FATF Recommendations.
Keywords: AML/CFT; Anti-money laundering; Botswana; Financement du terrorisme; Financial law; LBC/FT; Lutte contre blanchiment de capitaux; Money laundering

Challenges and solutions for the harmonisation of contract law within the BRICS countries. Invalidity of contracts and hardship - Veronese, Lígia Espolaor (Universidade de São Paulo, 2021)
The present thesis is concerned with a comparative study of contract law applicable in the BRICS countries Brazil, Russia, India, China and South Africa with a strong focus on the issues of invalidity of contracts and hardship. The purpose is to identify commonalities and divergences in these systems with different legal backgrounds, particularly the influence of civil law tradition in Brazil, Russia and China as opposed to common law in India, and the mixed system in South Africa. Among the identified divergences and challenges, the thesis purports to demonstrate that the obstacles are not insuperable and that there are rooms for the harmonisation and compatibility within the BRICS context with respect to the two selected topics of contract law. Even when full harmony is not reached, the research also purports to demonstrate that some countries may benefit from others divergent experiences. Detecting mutual contribution is of particular relevance to this group of countries, since they share the characteristic of being evolving systems which have undergone recent reforms in their legislation on contract law and may be more open to assess and incorporate more efficient contract practices.
Keywords: BRICS; Brazil; Common law vs. Civil law; Comparative law; Contract law; Contribuição; Contribution; Direito comparado; Direito contratual; Hardship; Harmonisation; Harmonização; Invalidade dos contratos; Invalidity of contracts; Russia; South Africa; Validade dos contratos; Validity of contracts

The (Domestic) Enforcement of AU International Economic Law Instruments: Exploring the Desirability of Direct Effect - Simo, Regis Yann (The Emergent African Union Law: Conceptualization, Delimitation, and Application, 2021)
This chapter deals with the principle of direct effect as applied in European Union law and explores its suitability in the enforcement of African Union (AU) legal instruments, notably those setting up the African Continental Free Trade Area (AfCFTA). What motivates the issue of direct effect is the noted reticence of African countries to litigate trade matters between themselves despite the existence of provisions of regional trade treaties creating courts of justice which give standing to Member States. Therefore, it surveys the avenues through which natural and legal persons can uphold their rights stemming from AfCFTA treaties thus contributing to treaty interpretation and increasing security and predictability. Currently, the AfCFTA Dispute Settlement Protocol, modelled after the WTO, does not allow such a possibility, contrary to rights acquired by natural and legal persons before some African Regional Economic Communities (RECs) courts. Nevertheless, this chapter finds that carving out access of natural and legal persons to AfCFTA proceedings may not always work as intended since there are other ways to bypass these obstacles. These loopholes could be the gateway through which direct effect will develop and become a principle of AU law broadly speaking. These gaps further complement this chapter’s suggestions to explore amending the AfCFTA legal instruments, even though its dispute settlement system is yet to be tested, in order to match the standing that natural and legal persons have acquired under the RECs, which, in fine, are building blocs towards achieving the AfCFTA and, eventually, the African Economic Community.
Keywords: AfCFTA; Africa; Direct effect; International Economic Law; International Law; International Trade Law; Regional courts; Regional integration

Soft Law in International Investment Law and Arbitration - Adinolfi, Giovanna (The Italian Review of International and Comparative Law, 2021)
In the more recent decades, international investment law (“iil”) and arbitration have been going through a process of recalibration prompted by both the intensification of cross-border capital flows and the States’ growing concerns over the potential restraints iil may impose upon the pursuit of public interests. The present contribution will pay attention to a specific feature that can be observed within these developments, i.e. the role played by soft law in investment arbitration and, more generally, under iil, also with a view to assessing the impact on the formation of binding international law of instruments formally devoid of normative force within the international legal order. After an introduction (Section 1), the contribution is articulated into four sections. Section 2 will first define the field of investigation. The case law of investment tribunals and the treaty practice under the more recent iia s will be then explored as to the reliance on soft law instruments for the purposes of settling procedural (Section 3) and substantive issues (Section 4). Some final remarks will close (Section 5).

Arbitration as a Legal Mechanism in the Settlement of Disputes under Cameroonian Law - Tambe, Hans; Forbi, Nduah Esther; Epie, Mousinga Adele (Social Science Research Network, 2021)
Recently, commercial activities in the state of Cameroon are evolving and there is an inflow of investors from within the OHADA Zone and other regions of the world to Cameroon. This has led to the proliferation of commercial contracts such as concession contracts, production sharing agreements, risk contracts between the Republic of Cameroon and foreign investors, or contracts between individuals of foreign countries as well as with Cameroonian nationals. Commonly, contracts may be breached and disagreements surface among the contracting parties. The difficulties pose is in the manner to settle such disagreements in a friendly manner to maintain the relationship between the parties and to enables the contracting parties to resolve the disputes more cost-effectively and increase business efficiency in Cameroon. However, the state of Cameroon has a favorable attitude towards bilateral and multilateral investment treaties to guarantee protection to investors in the territory. This elucidates the reason why the government of Cameroon has enacted laws and ratified regional and international treaties, aimed at safeguarding a smooth atmosphere for investors and other commercial traders particularly in the domain of arbitration to help in resolving disputes in case of any disagreement among contracting parties. This article will present the authorities involved in arbitration with the experience regarding the application of the various law and institutions concerned with the arbitration. This will also help contracting parties or investors to understand the legal mechanisms in the settlement of disputes through arbitration in Cameroon.
Keywords: Arbitrage; Arbitragem; Arbitration; dispute; legal; mechanism; settlement

Legal Guide on Agricultural Land Investment Contracts - UNIDROIT; IFAD (UNIDROIT/IFAD, 2021)

Firm Performance, Financial Constraints, and Dual-Class Share Structure - Ahamed, Fatematuz Tamanna (Victoria University of Wellington, 2021)
This thesis addresses two aspects of financial constraints focusing, firstly, on the impact of financial constraints on firm performance and, secondly, on the impact of dual-class share structure on financial constraints. The first issue has been addressed in a large number of research studies, but the results are mixed. This study, therefore, conducts a meta-analysis of those earlier studies to provide a summary view of the results which, in contrast to narrative reviews of the empirical literature, provides an objective overview. The second issue examines the impact of dual-class share structures on financial constraints. The period of the global financial crisis is used to test the impact of the state of the economy on that relationship. To examine the impact of financial constraints on firm performance, 26 empirical studies with 189 effect sizes representing listed firms have been analysed. The study finds that overall there is a positive relationship between financial constraints and firm performance. The study also shows that the set of market-based measures of firm performance has a significant negative impact on the relationship, compared with the set of accounting-based measures. In terms of the financial constraints measure, the set of external financial constraints measures have a positive and highly significant impact on the relationship. The meta-regression analysis suggests that the choice of measure, regional difference, journal quality and publication status all have a significant impact on the relationship, and explain the variation in the association. To examine the impact of dual-class share structures on financial constraints the study analyses a sample of non-financial US firms over the period 2002-2018. Share structure is measured by the existence of a dual-class structure and also by excess voting rights and the proximity of the superior class shareholders in such structures. The study also shows that if financial constraints are measured by the WW index, irrespective of how dual-class share structure is measured, it increases the level of financial constraints. Similar results are obtained where financial constraints are measured by the KZ and SA indexes, except where dual-class share structure is measured by the proximity of superior class shareholders. The study also finds that if financial constraints are measured by the WW index, dual-class had a reduced impact during the period of the global financial crisis, thus, providing support for the propping theory. However, if financial constraint is measured by the SA index, dual-class share structure appears to have an increased impact during the GFC years. Among the additional tests, the HM index has been used as a measure of financial constraints, and the findings show that the impact of dual-class structures on financial constraints appears to be driven by their effect on debt constraints. The study also shows that firm age moderates the impact of dual-class share structures if financial constraints are measured by the WW index. The KZ, WW, and SA indexes are based on firm characteristics and, therefore, the study also tests for an impact of dual-class structures when financial constraint is measured by a text-based index, the BLM index. However, the results do not provide evidence of an impact in that case.
Keywords: Dual-class share structure; Financial Accounting; Financial Constraints; Firm Performannce; Meta analysis

Comparison of Egyptian and English Mediation Procedures in Construction - Swelam, Ahmed; Eldosouky, Adel Ibrahim; El Korany, Tamer Mostafa (Journal of Engineering Research, 2021)
The mediation process is the parties' will to the dispute to reach an amicable, non-binding settlement to end their dispute. The Egyptian legislature adopted the idea of issuing a draft law on mediation in civil and commercial matters to settle disputes between the parties, whether before the litigation stage or after appearing before the courts. The Egyptian Ministry of Justice held many community dialogue sessions to find the final version of the draft law. However, the concerned authorities have not issued the law until writing this paper. This research aims to compare and analyze the Egyptian mediation procedures and the British mediation procedures to improve, develop, and enhance the Egyptian ones especially the draft law as well as overcoming the obstacles that hinder the spread of mediation. On the one hand, presenting the Egyptian procedures in the draft mediation law and the rules of the Cairo Regional Center for International Commercial Arbitration, CRCICA. On the other hand, the British procedures represented in the Institute of Civil Engineers' mediation rules, ICE.
Keywords: Egypt; England; Mediation

Big Data and Global Trade Law - Burri, Mira (Cambridge University Press, 2021)
This collection explores the relevance of global trade law for data, big data and cross-border data flows. Contributing authors from different disciplines including law, economics and political science analyze developments at the World Trade Organization and in preferential trade venues by asking what future-oriented models for data governance are available and viable in the area of trade law and policy. The collection paints the broad picture of the interaction between digital technologies and trade regulation as well as provides in-depth analyses of critical to the data-driven economy issues, such as privacy and AI, and different countries' perspectives. This title is also available as Open Access on Cambridge Core.
Keywords: AI; Artificial Intelligence; Big data; Blockchains (Databases); Data protection––Law and legislation; Foreign trade regulation; Inteligência artificial; Intelligence Artificielle; Law and legislation; Transborder data flow––Law and legislation.; World Trade Organization

The inclusion and assessment of climate related and environmental related risks in the banking industry: the UniCredit case. - Gioia, Giovanni Luigi (LUISS Guido Carli, 2021)
The nexus between climate-related risks and financial risk. From nuclear to climate apocalypse. The turning point: Paris agreement and UN 2030 agenda for sustainable development. The VUCA world. The European Union as pioneer of ESG revolution. Climate-related risks in the banking sector. The EBA framework of ESG risk for financial institutions. The principles for responsible banking. Environmental-related risk assessment. The mispricing of the environmental-related risks. The environmental-related disclosure as a risk mitigation tool. How do UniCredit assess, monitor and mitigate climaterelated risks. UniCredit’s financial risk management framework. Comparison with KPMG benchmark.

Post award arbitral tribunal's mandate under the UNCITRAL Model Law and national laws based thereon - Al Hyari, Omar Hisham; Al Ani, Abdullah Rabee (Heliyon, 2021)
The UNCITRAL Model Law on International Commercial Arbitration provides for the extension of the mandate of the arbitral tribunal post issuance of the final award for the issuance of correction, interpretation, additional award, and remittance of the award back to the arbitral tribunal to remove grounds for challenging the award. Using a doctrinal approach, this paper examines the deviations of the national laws of adopting jurisdictions from the Model Law in regards to this extended mandate, and evaluates the improvements and drawbacks in these deviations. Mainly, the findings of this paper are that, of the many deviations, the positive changes are those that provide comfortable and lenient default provisions for the benefit of inexperienced parties, and since correction, interpretation, additional award, and remittance are useful provisions that are designed to help self-rectify the arbitral process, without adversely delaying it, then the changes that increase the efficacy of these provisions are welcomed. On the other hand, unnecessary deviations are seen as drawbacks that hinder the harmonization of national arbitration laws aimed at by the Model Law. The adopting jurisdictions shall be limited to those acknowledged as such by the UNCITRAL.
Keywords: Additional award; Arbitrage; Arbitragem; Arbitration; Arbitrators' mandate; Award; Correction; Interpretation; Model Law jurisdictions; UNCITRAL Model Law

Reasonable awareness in compensation for infringement of IP rights - Vanbrabant, Bernard; Glorieux, Dietger (Revue de Droit Intellectuel. L'Ingenieur-Conseil, 2021)

Value Relevance of Integrated Reporting using a Novel Approach: Comparative Cross Country Evidence of Mandatory and Voluntary Implementers - Mohaimen, F. J. (Victoria University of Wellington, 2021)
This thesis examines the value relevance of accounting information under integrated reporting (IR) in a comparative mandatory and voluntary setting. A meta review is conducted of all published work focusing on integrated reporting since 2011, which provides detailed insight into the gaps in the IR literature. Multiplicative log-linear model is used in measurement, which is a novel technique that mitigates the shortcomings of traditional value relevance models. The findings show that value relevance of summary accounting information increases after the implementation of IR in the mandatory setting. In the voluntary setting, market effect and the existing reporting paradigm effect the value relevance of accounting information under IR. If the market is large and existing reporting requirements are robust voluntary adoption of IR has minimal to no effect. However, in smaller markets with less rigorous reporting environment, adoption of IR does result in increased value relevance of accounting information. Compared to traditional models, the multiplicative model provides estimates that are more stable over time and shows better explanatory power. Overall, the findings of this thesis show that capital providers value the information content of IR under specific circumstances. This thesis contributes to the IR and value relevance literature by providing the first comparative cross-country evidence of the effect of IR in the change in value relevance of reported accounting information. It provides policy relevant input to the standard setters of IR by demonstrating the effect of IR in the decision usefulness of summary accounting information. The thesis further provides robust evidence of the efficacy of using the multiplicative log-linear model in measuring value relevance instead of the traditional linear additive models.

Compensation for Regulatory Expropriation in International Investment Law - Khachvani, David (Université de Genève, 2021)
The States, international organizations and interest groups are increasingly concerned with treaty claims of foreign investors, who sometimes seek compensation for the States' legitimate regulatory measures, such as tobacco plain packaging, nuclear energy phase out and environmental regulations. International investment law has yet to develop a comprehensive and predictable framework addressing some of the basis questions related to compensability of legitimate regulatory measures. The thesis carries out a comparative legal analysis to identify the key features of the prohibition of uncompensated expropriation as a general principle of law, and explores the rationale of that principle in political philosophy. Equipped with the results of this analysis, it proceeds to propose an analytical approach addressing practical questions related to the compensatory protection of foreign investments.
Keywords: Climate Change; Compensation; Expropriation; Investments; Police Powers; Regulatory Powers

Legal Protection of Foreign Direct Investment in the OHADA Area - Ngoya, Dominique (Social Science Research Network, 2021)
This paper analyzes the protection of Foreign Direct Investments in the OHADA area, specifically, its regulation by the Treaty of Organization and Harmonization in Africa of Business Law (OHADA Treaty). It is to restore legal and judicial security within their scope that OHADA member countries have undertaken to harmonize and unify their economic sector legislation to attract foreign investment as a factor in economic development. Several national and international legal instruments are responsible for the protection of foreign direct investment in OHADA countries. Indeed, the volume of foreign direct investment (FDI) to developing countries increased considerably during the 1990s; As Africa is now one of the favorite destinations for Western and even African investors, it is becoming a very profitable continent for investors. However, the issue of regulating or securing foreign investment in African countries is still flawed. The establishment of OHADA, in a way, is in the same direction; if we stick to the purpose of the organization prescribed in paragraph 5 of the preamble to the OHADA Treaty, which states that the purpose of the OHADA law is to "promote the growth of economic activity and encourage investment." Unfortunately, this objective remains only an announcement of the preamble to the Treaty, because of the definition of business law given by Article 2 of that treaty. However, the list of subjects is not exhaustive, investment remains absent. Thus, foreign investment is not regulated by the OHADA Treaty, so even investment-related activities are held by other subjects (corporate law, commercial law, and security law). The omission of FDI in the scope of the OHADA Treaty leads us to raise the question of its regulation.This work proposes a reflection that the OHADA Treaty should be modernized through reform including investment and many other issues to deal effectively with the issue of foreign investment given the ineffectiveness of national and sub-regional instruments in this area.
Keywords: Foreign direct investment; Investment Law; Investment Protection; OHADA

A developing country's perspective on forum shopping and long arm jurisdiction in light of US and UK insolvency laws - Gatoto, Phoebe Njoki (Nottingham Trent University, 2021)
The trend for multinational companies has been a preference to forum shop rather than to open insolvency proceedings in developing countries. The US and the UK are prime venues for such bankruptcy tourism enabled by long-arm jurisdiction through extraneous connection. At the same time, there has been a pattern in developing countries of insolvency law reforms which have been circumvented when multinational companies forum shop. Using doctrinal and comparative methodologies, this thesis examines how forum shopping and long-arm jurisdiction to the US and UK affect the efforts of developing countries to reform their insolvency laws and their possible effects on local stakeholders of multinational companies in developing countries. Additionally, the thesis proposes a longer-term strategy of dealing with forum shopping and long-arm jurisdiction by using the concept of centre of main interests ('COMI') as the basis for opening main insolvency proceedings. To ensure that the proposed insolvency procedural legal law is implemented uniformly, the thesis proposes the creation of a supranational court from which national courts, insolvency practitioners and multinational companies can request clarifications on the provisions of the proposed insolvency procedural legal framework. The thesis identified that developing countries require effective insolvency laws and institutions and highlighted key principles that should be included in the reforms. The hope is that developing countries can improve their insolvency laws and institutions to a global standard. Once the proposed insolvency procedural legal framework is implemented, multinational companies will be encouraged to utilise them once jurisdiction is identified through the COMI test rather than forum shopping.

La publication des informations sociétales suivant les lois comptables revisées OHADA - Guimezap Épse Choukem, Claire (Revue Française d'Economie et de Gestion, 2021)
Dans un contexte marqué par le développement durable, le législateur OHADA n’a eu de cesse d’être accablé de toutes parts pour son statisme vis-à-vis de la montée des problématiques sociétales. Au lendemain des reformes du système comptable OHADA, les problématiques sociétales ont une fois de plus raté le rendez-vous de la normalisation. Toutefois, de nombreuses entreprises continuent à publier leurs informations sociétales parallèlement à leur communication financière. A cet effet, le problème que soulève cet article est celui de la compréhension des modes de production et de diffusion des informations extra-financières en l’absence d’une réglementation en la matière. Une étude empirique de nature descriptive est menée auprès d’un échantillon de 120 entreprises diffusant leurs informations sociétales au sein de l’espace OHADA. Il en ressort que le site internet et l’implication dans le développement de la communauté locale sont apparue respectivement comme support et thème de diffusion les plus utilisés dans l’espace OHADA en matière de reporting sociétal sous la pression de certaines parties prenantes notamment les associations consuméristes, les départements ministériels en charge de l’environnement, du travail et de la sécurité sociale. In a context marked by a widespread awareness of the needs of sustainable development, the OHADA legislator has been constantly burdened on all sides for its statism to the rise of societal problems. However, After the reform of the OHADA system, sustainability problems once more did not met up with the appointment of normalization. However, several enterprises continue to publish their societal information in parallel with their financial communication. As such, the problem raised by this article is that of understanding the mode of production and disclosure of non-financial information in the absence of a regulatory framework. A descriptive empirical analysis is carried out with a sample of 120 enterprises which propagate their societal information in the OHADA zone. It reveals that internet websites and implication in the development of the local community are respectively the medium and theme of the most used disclosures in the OHADA zone with regards to sustainability reporting under the pressure of some stakeholders especially consumer associations, ministerial departments in charge of the environment labor and social security.
Keywords: Accounting law; CSR; Corporate Social Responsibility; Droit comptable; Information sociétale; Parties-prenantes; RSE; Responsabilité Sociétale de l'Entreprise; Stakeholders

Corporate Social Responsibility, Corporate Governance and Banking Performance in the CEMAC Region - Fondem, Divine (Liberty University, 2021)
This researcher examined the effect of corporate governance (CG) and corporate social responsibility (CSR) on banking performance in the Central African Economic and Monetary Community (CEMAC) region. The data was obtained from the Worldwide Governance and the World Bank sovereign database from 2003 to 2018. This study employs the z-score to proxy the CSR factors such as labor force participation rate, population density, and renewable energy. The results reveal that the fixed effects model is superior to the pooled ordinary least square (OLS) and the random-effects model. The findings show that CSR has a significantly positive relationship, while CG has a positive but insignificant relation with banking performance in the CEMAC region. It suggests an ineffective implementation of CG strategies in the entire CEMAC region.
Keywords: Banking Performance; CEMAC; CSR; Central Africa Economic and Monetary Community; Corporate Social Responsibility; Corporate governance; RSE

Legal Challenges in the Enforcement of Foreign Arbitral Awards in Nigeria - Kudirat, Magaji (University of Ilorin, 2021)
Businessmen have a choice in the resolution of disputes, they may elect litigation or submit to arbitration. Delays, outrageous cost and undue technicalities associated with courts, makes commercial arbitration the preferred mode of settlement in the business world. However, the recalcitrance of an award-debtor to comply with the terms of the award necessitates the intervention of the courts. Nigeria has provisions for enforcement of foreign arbitral awards within her legal system. However, reliance on courts for enforcing foreign awards frequently frustrates the gains initially made by arbitration. Enforcement of arbitral awards via the courts has numerous legal challenges. This study is therefore aimed at analysing the challenges facing enforcement of foreign awards in Nigeria. The objectives of the study were to: (i) analyse the impact of extant legal regimes on the recognition and enforcement of foreign awards in Nigeria; (ii) examine the effects of the concepts of arbitrability and public policy exceptions on the enforcement of awards in Nigeria; (iii) examine the challenges inherent in judicial review on the enforcement of foreign awards in Nigeria; and (iv) examine the adequacy of the Arbitration and Conciliation Act 1988 (ACA 1988) in the recognition and enforcement of Islamic commercial arbitral awards. The study employed doctrinal methodology of legal research where primary and secondary of legal materials were subjected to descriptive and content analysis. The primary sources used were legislations, regulations, treaties, conventions and case laws, while secondary sources used were texts books, journals, internet materials, conferences and seminars papers. The findings of the study were that: i. the provisions of the laws regulating enforcement of foreign arbitral awards in Nigeria, particularly, Sections 51 and 54 of ACA 1988 have inherent and procedural defects, thus preventing the smooth enforcement of the award; ii. the narrow interpretation by the Nigerian courts on ‘arbitrability’ based on Sections 54 and 57 of ACA 1988 which restricts disputes to contractual and commercial disputes only, prevents the enforcement of foreign awards from jurisdictions with liberal interpretation. iii. the amorphous nature of the scope of public policy creates a challenge for the courts in Nigeria in determining whether a foreign award violates the country’s public policy or not; iv. the powers of the courts to set aside foreign awards based on grounds contained in Sections 29, 30 and 48 ACA 1988 are open-ended and allow the courts to examine the merit of the disputes rather than limit themselves to the validity of the award for enforcement; v. the provisions of ACA 1988 on enforcement of foreign arbitral awards do not consider the idiosyncrasies of awards from Islamic law jurisdictions, despite growing investors’ interests in Islamic commercial transactions. The study concluded that it is obvious that the various legal challenges identified showed that the existing legal frameworks on enforcement of foreign arbitral award in Nigeria are weak and ineffective. The study therefore recommended that the Nigerian arbitral laws in particular, the provisions on enforcement of arbitral awards under ACA 1988 should be amended.
Keywords: Enforcement; Foreign Arbitral Awards; Legal Challenges; Nigeria

The Role of Alternative Dispute Resolution (ADR) in Dispute Settlement of Logistics Activities - Quan, Gao (International Journal of Trend in Scientific Research and Development, 2021)
The Alternative Dispute Resolution (ADR) provides a non-litigation settlement mechanism for the parties of logistics activities. The advantages of ADR are highlighted in logistics dispute resolution due to the characteristics of logistics dispute and the difficulties faced in the litigation procedure. In the dispute resolution process, ADR means a simple, cost-efficient, and convenient method for the parties involved to settle disputes quickly, flexibly, and friendly. With its legitimacy and rationality, ADR should be the preferred choice for the parties involved in logistics dispute resolution.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitragem; Arbitration; Dispute settlement; Litigation procedure; Logistics activities; MARD; Mediación; Mediation; Mediação; Médiation

The legal nature of debt securities in South African law - Beer, Johan Philip de (Stellenbosch University, 2021)
The problem statement of this thesis is ascertaining the legal nature of debt securities in furtherance of a consistent and coherent legal description of the South African positive law as it relates to this class of instruments. It focuses on four core issues: the legal history, legal nature, classification, and current legal issues relating to debt securities. Historical and analytic-systemic approaches to the problem statement make up Part 1 of the study. The historical approach shows an emergent commoditisation of debt, which is an important phenomenon in the analysis of securities law. It further shows a great deal of English influence in the development of the South African legal environment, most notably in terms of company law (as the primary driver of securities law) and the financial marketplace, its institutions and its regulation. Also highlighted is a notable scarcity of debt securities relative to equities, which materially impacted legislative developments. Finally, it points to an increase in the legal importance of the “securities” concept as a legal term to describe and govern debt and equity securities. Thereafter the analytic-systemic approach is used to identify a set of private law-rooted first principles applicable to South African registered securities, and herefore to debt securities as well. It posits that these securities should be understood conceptually as comprised two interdependent but functionally separate legal objects, rather than in terms of two different kinds of ownership (i.e. beneficial and registered). The first object is the "security instrument”, a locus for (holdership of) the incidents that flow from the entitlement of determination (beskikkingsbevoegdheid) over the underlying complex of rights and competencies of registered securities. These can be understood as incidents of execution. The second is the "security asset”, a locus for (holdership of) the incidents that flow from the entitlement of enjoyment (genotsbevoegdheid) over that underlying complex, and corresponds with the proprietary, patrimonial dimension of securities. These can be understood as incidents of enjoyment. This construction enables a more coherent understanding of the sui generis relationship of agency between beneficial owner and her nominee, as well as of the dynamics of ownership and quasi-possessio. These insights are then applied to the uncertificated environment, addressing a number of difficult and uncertain problems within the system that enables uncertificated securities and their holdership. Finally the particularly difficult issue of how to classify (and therefore identify) debt securities is dealt with. Here it is concluded that a typological approach is the only viable methodology to deal with this problem, and a number of necessary and thereafter possible classificatory indicia are outlined for this purpose. The functional-policy approach makes up Part 2 of the study. It is a policy-aware application of the theoretical framework developed to a select number of themes and legal issues of the current environment. Principally it shows that the reconceptualisation of registered securities has explanatory and problem-solving value, specifically relating to transfer, the granting of limited real interests, good faith acquisition, and the protection of holdership of certificated and uncertificated securities.
Keywords: Beneficial ownership; Debt and equity Securities; Securities; Securities industry; South Africa; Titre de créance

Mediation: Is There a More Promising Future? The Case of the Cairo Business Community - Soliman, Cherine (Arab Journal of Administration, 2021)
In an era of economic distress, some organizations have found refuge and growth potential in cooperation. Mediation, a highly recommended cooperative concept, has been enabled in certain countries but not all. Some applications lacked local cultural support making it, despite government efforts, a failure to launch. In this article, we investigate attempts to launch mediation in the Cairo Business Community (CBC). This study enabled us to revisit how Egyptian culture was prototyped by Hofstede and to question its representativeness. Hofstede has consistently described Egyptian culture as being highly cooperative / collectivist but our observations indicate that this culture is now more of an individualistic / competitive type, due to the tremendous economic difficulties that Egyptian society is going through. These difficulties and their impact on culture are at the heart of the explanation of the failure to launch mediation in the CBC.
Keywords: Cairo Business Society; Conflict Resolution; Culture; Egypt; Mediation

Combating insolvency and business recovery problems in the oil industry: proposal for improvement in Nigeria's insolvency and bankruptcy legal framework - Olujobi, Olusola Joshua (Heliyon, 2021)
Insolvency and business recovery laws in Nigeria have not evolved to incorporate reorganisation, reforming insolvent oil firms' operations to boost commercial oil firms' steadiness and economic suitability like other moderately developed countries. In Nigeria, liquidation is understood by many as the panacea to indebtedness. The research evaluates the Nigerian insolvency and business recovery legal regime to sustain indebted oil firms from economic shocks due to the global decline in the oil price to avert imminent business failures due to insufficient cash flows. The aim is to fill the gaps in Nigeria's insolvency and business recovery laws by recommending a model for the sustenance of oil firms and to suggest the reform of the gaps identified in the existing laws and the extant literature on the subject. The paper opted for conceptual legal review, comparative legal and policies analyses of solvency and business recovery legislations in Nigeria, Malaysia, India, South Africa, the United Kingdom and the United States. These nations were designated for this study because their insolvency and business recovery legal regime are business rescued driven, not winding up centred. The study is library research-based to address some of the flaws in Nigeria's insolvency and business recovery laws. The study finds that Nigerian legislation on insolvency is flawed in oil firms' salvage, improvement and rearrangement. It ends that, statutory bodies in the designated case study nations are efficient than those in Nigeria due to the strong political will of their governments in supporting insolvent oil firms for successful financial recovery, to safeguard jobs, to protect creditors and to enhance the wealth of their nations through sound business recovery policies and laws. The study, advocates, remodel of Nigeria's insolvency and business recovery legislations and policies in compliance with the international standards on insolvent oil firms salvaged and creditors focused policies for a robust economy. The study concludes with the recommendation for further study to consider quantitative analysis research methodology to project further scholarship on the subject.
Keywords: Creditor; Insolvency and business recovery laws; Nigeria; Oil firms

The impact of multilateral trade agreements on intra-regional trade : the case of SADC and ECOWAS - Osarumwense, Uwakata Yvonne (University of South Africa, 2021)
This study examines the comparative impact of multilateral trade agreements on intra-regional trade in the Southern African Development Community (SADC) and the Economic Community of West African States (ECOWAS) regions in Africa. Annual data was gathered from 2000 to 2018 and dynamic panel data and econometric techniques were used to control for individual country characteristics, endogeneity, serial correlation, heteroscedasticity and interdependencies between the countries in each region. Two estimations were done, one using the tariff measures of multilateral agreements, the second using non-tariff measures of multilateral agreement. The results of the empirical analysis show that the SADC region has a slight edge over ECOWAS in terms of technological progress and investment, especially in trade infrastructure. However, the ECOWAS levels of employment and economic growth are higher than those in the SADC region. These differences further translate into differences that drive intra-African trade in these regions, and how they relate to the role of multilateral agreements in intra-African trade in each of these regions. While technology and investment are key drivers and enhancers of intra-African trade in SADC countries, economic growth and employment stand out as key enhancers of intra-African trade in ECOWAS, especially where multilateral agreement is represented by tariff measures. This study reports that when non-tariff measures are used to represent multilateral agreements, export trade costs, in addition to investment and technology, are the key drivers of intra-African trade in SADC countries. For ECOWAS, under non-tariff measures of multilateral agreements, only economic growth drives intra-African trade.
Keywords: Commercial treaties; Customs unions; Institutional environment; Intra-African trade; Investments; Multilateral agreement; Panel data estimation; Tariff and non-tariff trade barriers

The Impact of Trade Openness and Foreign Direct Investment on Economic Welfare in sub-Saharan Africa - Adegboye, Folasade Bosede; Adesina, Olumide Sunday; Olokoyo, Felicia Omowunmi; Ojeka, Stephen Aanu; Akinjare, Victoria Abosede (International Journal of Financial Research, 2021)
The sub-Saharan African region is characterized by a high relative degree of openness to trade. The region is also identified with increased inflows of foreign investments with no significant welfare improvement. Economic development emphasizes that the lack of domestic investment in the developing economies could be boosted by trade openness and inflow of Foreign Direct Investment (FDI) for impactful enhancement of capital formation. In this article, the impact of trade openness and foreign capital inflow on economic welfare was examined on a sub-regional analysis for sub-Saharan Africa. The study also appraised the effect of openness to trade and FDI inflow on the region's economic welfare. The data for 30 countries from 2000 to 2018 were collected and analyzed, with the Generalized Least Square (GLS) technique to fit the model developed. The study showed that openness to trade has a significant impact on economic welfare for all sub-Saharan Africa regions, while FDI is only significant for the Western sub-region. Hence, the study recommends that the government of the countries in the sub-Saharan Africa region should boost trade openness to enhance efficiency in productivity, and improve industrial development.
Keywords: Economic Welfare; Foreign direct investment; Sub-Saharan Africa; generalized least square; sub-regional analysis; trade openness

The influence of capital structure and profitability on the solvency of nascent SMEs - Amoa-Gyarteng, Karikari (University of Johannesburg, 2021)
Even though small and medium enterprises contribute significantly to the growth of national economies, they are vulnerable in their early stages and may fail. Hence younger businesses are more likely to fail than more established ones because they face complex challenges that may limit their viability. This is a notion established in the liability of newness framework. According to the liability of newness concept, the precarious existence of emerging organisations is due to difficulties in managing relationships among strangers, not quickly assembling resources, and not coping with difficult environments, among other issues. All these elements notwithstanding, previous literature suggests that small businesses can, and sometimes do engage in techniques or approaches to help reduce the liability of newness, such as raising adequate capital. This study suggests that not only is adequate capital important but that the right mix of capital also results in higher solvency, thereby mitigating the liability of newness. Because the various funding forms have distinct advantages and disadvantages, an appropriate capital structure reduces the cost of financing while increasing the value of the firm. This study also advances the idea that profitable businesses are productive and financially strong, and thus nascent enterprises with high profitability can minimise the liability of newness. As a result, the study sought to examine the influence of capital structure and profitability on the solvency of nascent small and medium enterprises. To put the study's hypotheses to the test, 1106 nascent small and medium enterprises that are registered with the National Board for Small Scale Industries were sampled across three major cities in Ghana. Thus, data was gathered from every member of the population. Such data, gathered from the SMEs' financial statements, was submitted to preliminary screening as well as a number of statistical measurements. Operationally, the dependent variable, solvency, was defined as the solvency ratio, working capital ratio, and net worth. As a result, three distinct regression models were developed for robustness. The study's findings broadly indicate that capital structure and profitability have an influence on the solvency of nascent small and medium enterprises. The study also determined that emerging small and medium enterprises should follow the principles of the pecking order theory to reduce the liability of newness. These findings, if adopted by SME owners, can aid in the maturation of their fledgling businesses.
Keywords: Entrepreneurship; New business enterprises

Proceedings of 2021 UNCITRAL Working Group III inter-sessional meeting: the use of mediation in ISDS - Asian Academy of International Law Limited (AAIL) (Asian Academy of International Law Limited, 2021)
Keywords: Dispute settlement; Investment disputes; MARD; Mediación; Mediation; Mediação; Médiation; UN Commission on International Trade Law; UN Convention on International Settlement Agreements resulting from Mediation (2018)

Securities regulation, enforcement and market integration in the development of sub-Saharan Africa's capital markets - Aziza, Onoriode Reginald (University of Oxford, 2021)
This thesis examines securities market development in sub-Saharan Africa, focusing on securities law, securities law enforcement and securities markets integration. Adopting a primarily comparative methodology, the thesis examines the continued relevance of securities markets in sub-Saharan Africa; the way selected countries in the region regulate their markets and enforce compliance with securities law; and the potential of market integration to promote market development. This thesis advances 4 main claims. First, empirical evidence supports the link between liquid securities markets and economic growth, independent of the level of banking development. In this sense, securities markets can act as good complements to banks in providing capital to the real economy. Second, at the minimum, there is an arguable preliminary case that rules of securities regulation can hinder market development in select countries in sub-Saharan Africa, by imposing high compliance costs and eligibility requirements, without commensurate benefits in greater liquidity or reduced cost of capital. Third, enforcement of securities regulation in sub-Saharan Africa is generally weak. Whilst public regulators often have formal powers, budgets and staff; actual enforcement activity is sometimes limited by inadequate market monitoring and reliance on criminal as opposed to administrative sanctions. Poor public enforcement, in turn, reinforces poor private enforcement, leading to reduced market participation, illiquidity, and ultimately market underdevelopment. Fourth, although increased market integration can go a long way in facilitating market development in the region, integration cannot be a short/medium term solution to market underdevelopment in sub-Saharan Africa, given the significant economic, political and socio-cultural barriers to integration initiatives in the region. Ultimately, to develop their securities markets, policymakers in sub-Saharan Africa must focus their attention on making and credibly enforcing market-friendly rules of securities regulation. The thesis explores some ways this may be realistically accomplished.
Keywords: Africa; Capital Markets; Capital market; Developing countries; Fintech; Going public (Securities); Market Integration; Securities; Securities Law; Securities Law Enforcement; Sub-Saharan Africa

A constitutional analysis of a differentiated tax treatment of residents and non-residents in respect of income deriving from immovable property in South Africa - Baines, Daniel (University of Pretoria, 2021)
A constitutional analysis of a differentiated tax treatment of residents and non-residents in respect of income deriving from immovable property in South Africa', Daniel Baines explores whether South African resident taxpayers' constitutional rights to equality and property are infringed by current laws which tax residents at higher rates than non-residents on rental income and proceeds from the disposal of fixed property. He aptly sets out what the right to equality and property entails and how these relate to taxpayers. He finds that the higher effective tax rates paid by residents violates their constitutional right to equality. The thesis provides valuable insight into a resident's right to equality and property in terms of current tax rates and illustrates how current tax rates are unconstitutional. The recommendations brought forward contribute toward the discussion of how tax rates should be altered in order to ensure that residents' constitutional rights are no longer violated.
Keywords: Immovable property; Income tax; South Africa; Tax treatment

A critical analysis of the effect of the moratorium on property owners - Beekarun, Yasthil (University of KwaZulu-Natal, 2021)
No abstract provided.
Keywords: Business rescue

Legal Translaboration for Effective Intercultural Communication - Bell Mandeng, Adrien (Scientific Annals of Alexandru Ioan Cuza University, 2021)
The European-inspired bilingualism and bi-legal system in Cameroon lead to an irregular profile and may be interesting for the European Union (EU) in its quest for preservation of intercultural processes through translation. The Organization for the Harmonization of Business Law in Africa (OHADA) of which Cameroon is part is only affiliated to Civil Law. However, the two legal systems employed in Cameroon (where both Civil Law and Common Law are used) are based on a balance in what concerns the conceptual, epistemic and stylistic representation. Intercultural dysfunction is the consequence of the lack of methodology in legal translation. Collaboration between legal translators and practitioners is key to adopt an agreed-upon model in multilingualism.
Keywords: Culture; History; Intercultural communication; Legal translaboration; OHADA

The arbitration of internal trust disputes in English law: Legal challenges and pathways - Clover Alcolea, Lucas (McGill University, 2021)
The arbitration of internal trust disputes has attracted significant attention in the arbitration and trust law communities in recent years with draft clauses and rules produced by arbitral institutions, several states undertaking legislative reform in order to provide such arbitrations with a statutory basis and numerous scholars as well as practitioners writing articles on the subject. Such enthusiasm is justified on the basis that arbitration has several advantages over litigation, such as confidentiality, international enforceability of judgments, the ability to choose one’s judge and the power to tailor the procedure. Notwithstanding these advantages, trust arbitration has failed to make any great inroad into trust disputes due to the many novel and complex points of legal practice and theory which it entails. For example, although arbitration does not typically involve minors or legally incapable parties’ trusts do, and thus trust arbitration raises numerous due process and human rights concerns. Similarly, court supervision and enforcement of trusts is sometimes considered essential to the very nature of trusts and questions therefore arise concerning the extent to which arbitral tribunals could supplant courts in that regard. Another complication is that trusts are not contracts and questions therefore arise about how to bind individuals to a trust arbitration agreement, particularly as regards beneficiaries who may be unascertained, minor or legally incompetent at the time the trust was created. The aim of this thesis is to analyse and present potential solutions to these complications from an English law perspective, although other common law legal systems will be analysed where relevant
Keywords: Arbitrage; Arbitragem; Arbitration; Internal trust disputes

Optimising regulatory responses to consumer disempowerment over personal data in the digital world - D'Amico, Alessia (European University Institute, 2021)
This thesis addresses the problem of individuals’ lack of control over personal data in the digital world. It sheds light on market and regulatory failures that lie behind the status quo and proposes a framework to improve regulatory responses. The two regulatory regimes that are at the core of this thesis are EU data protection regulation, which protects individuals’ fundamental rights over data, and EU competition law, which safeguards the sound functioning of the market and consumers’ economic interests. Despite the existence of these two regulatory regimes, individuals do not have sufficient control over personal data collected by digital firms, whose control over large datasets is a factor contributing to market monopolisation. The thesis argues that one reason for the shortcomings of today’s regulatory framework is that the market failure is composed of a combination of factors, which are currently addressed by the different regimes relatively independently. This dichotomy hinders the development of an effective strategy to tackle the market failure in its entirety. The approach taken in this thesis is that by integrating the two regimes, it might be possible to close the gaps deriving from a narrow perception of their regulatory spaces. Hence, the thesis formulates a holistic approach, encompassing data protection regulation and competition law, designed to increase the effectiveness of the regulatory framework as a whole. Different dimensions of the regimes’ interrelation are analysed, to uncover new ways to harness their complementarity and minimise their inconsistencies and overlaps. The thesis looks at how the regimes can incorporate elements from each other to inform their policies and application of their rules, as well as developing a complementary enforcement strategy. The holistic framework ultimately allows both regimes to better tailor their regulatory responses to the functioning of the digital market and take account of the diverse elements that constitute the market failure they seek to correct.
Keywords: Data Protection; Personal data; Privacy

A comparative analysis between the Turkish Financial Reporting Standard for large and medium-sized entities and the OHADA accounting system - Diallo, Amadou Thierno (Sakarya Üniversitesi, 2021)
The rapidly growing bilateral and multilateral economic relationship between Turkey and African countries leads to the necessity of understanding each other's business and financial environment. Therefore, the accounting system as a fundamental tool for organizing and disseminating financial information should be accessible and understood by business actors and other stakeholders in these areas. Furthermore, the lack of study related to this subject has led us to carry out this comparative analysis between the two accounting systems by comparing financial statements prepared under each one and analyzing their main similarities and differences. The main purpose of this study is to highlight major differences and similarities between the SYSCOHADA and the FRS for LMSE. Also, the study is aimed to get a good understanding of both accounting sets and help practitioners and businessmen, and women operating in these places to have a good knowledge of the accounting regulations related to each country. On a topic basis and based on financial statements prepared following the SYSCOHADA rules and restated to be adapted to the FRS for LMSE, all main differences and similarities were thoroughly analyzed. Following the case study and the thematical analysis of different accounting topics, it can be understood that the two accounting sets differ to some extent due to philosophical approach on some topics such as the prudence principle where the SYSCOHADA, contrary to the FRS for LMSE, does not allow the recognition of potential profit resulting from currency translation gains related to receivable and payables until such profit becomes certain. However, these two sets also share some major similarities due to their proximity in some way to the IAS/IFRS. The effect of the main differences between the two sets can be noticed in the restated financial statements. The annual net income following the FRS for LMSE increased compared to the initial annual net income in the SYSCOHADA. Also, total assets and liabilities restated following the FRS for LMSE have decreased compared to the SYSCOHADA financial statements. Türkiye ile Afrika ülkeleri arasında hızla büyüyen ikili ve çok taraflı ekonomik ilişkiler, birbirlerinin iş ve finans ortamını anlama zorunluluğunu doğurmaktadır. Bu nedenle, finansal bilgilerin düzenlenmesi ve yayılması için temel bir araç olarak muhasebe sistemi, bu alanlardaki iş aktörleri ve diğer paydaşlar tarafından erişilebilir ve anlaşılabilir olmalıdır. Ayrıca bu konuyla ilgili çalışma eksikliği, iki muhasebe sistemi arasında bu karşılaştırmalı analizi, her biri altında hazırlanan finansal tabloları karşılaştırarak ve temel benzerlik ve farklılıklarını analiz ederek yapmaya yöneltmiştir. Bu çalışmanın temel amacı, SYSCOHADA ve BOBİ FRS arasındaki önemli farklılıkları ve benzerlikleri vurgulamaktır. Ayrıca, çalışma hem muhasebe standartları iyi anlamak hem de uygulayıcılara ve bu yerlerde faaliyet gösteren iş adamlarına her bir ülkeyle ilgili muhasebe düzenlemeleri hakkında iyi bilgi sahibi olmalarına yardımcı olmayı amaçlamaktadır. Konu bazında ve SYSCOHADA kurallarına göre hazırlanmış ve BOBİ FRS' ye uyarlanmak üzere yeniden düzenlenen mali tablolara dayalı olarak, tüm temel farklılıklar ve benzerlikler kapsamlı bir şekilde analiz edilmiştir. Vaka çalışması ve farklı muhasebe konularının tematik analizi sonucunda, iki muhasebe setinin bir ölçüde felsefi yaklaşım nedeniyle ihtiyat ilkesi gibi bazı konularda farklılık gösterdiğini anlaşılmaktadır. SYSCOHADA, BOBİ FRS'nin aksine alacak ve borçlara ilişkin kur farkı kazançları kaynaklanan potansiyel kârın kesinleşene kadar muhasebeleştirilmesine izin vermemektedir. Bununla birlikte, bu iki muhasebe seti, UFRS/UMS'ye bir şekilde yakın olmaları nedeniyle bazı önemli benzerlikleri de paylaşmaktadırlar. İki sistemin temel farkların etkisi, yeniden düzenlenen mali tablolarda fark edilebilir. BOBİ FRS'yi takiben yıllık net gelir, SYSCOHADA'daki yıllık net gelire kıyasla artmıştır. Ayrıca, BOBİ FRS'yi takiben yeniden düzenlenen toplam varlıklar ve yükümlülükler, SYSCOHADA finansal tablolarına kıyasla azalmıştır.
Keywords: Accounting standards; Accounting systems; Büyük ve orta boy işletmeler için finansal raporlama standardı; Comparative analysis; Financial reporting standard for large and medium size enterprises; Financial reporting standards; Finansal raporlama standartları; Karşılaştırmalı analiz; Muhasebe sistemleri; Muhasebe standartları; Turkish Financial Reporting Standards; Türkiye Finansal Raporlama Standardı

Transition from Local Accounting Standards to International Accounting Standards: A Comparison Between the OHADA Member Countries and Turkey - Diallo, Amadou Thierno; Çevi̇K, Zülküf (Yorum Yönetim Yöntem Uluslararası Yönetim Ekonomi ve Felsefe Dergisi, 2021)
This study tries to get a clear grasp of the factors that might play positively or negatively in a country’s convergence or adoption of the international financial reporting standards (IFRS). Through a comparative analysis between Turkey and the OHADA countries and based on the existing literature, the transition process towards the IFRS and challenges faced by each one is discussed from a historical perspective to the level of development. As a result, it is understood that the adoption or convergence towards the IFRS can be a challenging and a long-term process requiring multiple adjustments. Also, countries may differ in terms of historical past, level of development, cultural and socio-economic aspects which can all influence their transition. In addition, given the lack of study on the new adoption of the IFRS in the OHADA countries, this paper will contribute to filling the gap in the literature on the transition process. Furthermore, it will help countries which are in their early stage of the transition process to avoid some missteps and learn from others experience to get better prepared for a successful shift towards a fully IFRS compatible accounting system as has done Turkey. Bu çalışma, bir ülkenin uluslararası finansal raporlama standartlarına (IFRS) yakınsaması veya tam olarak benimsemesinde olumlu veya olumsuz rol oynayabilecek faktörleri tespit etmeyi amaçlamaktadır. Türkiye ile OHADA ülkeleri arasında karşılaştırmalı bir analiz yoluyla ve mevcut literatüre dayalı olarak, UFRS'e geçiş süreci ve bu süreçte karşılaşılan zorluklar, tarihsel bir perspektiften tartışılmaktadır. Sonuç olarak, IFRS’in benimsenmesi veya uyumlaştırılmasının zorlu ve birçok ayarlama gerektiren uzun vadeli bir süreç olduğu anlaşılmaktadır. Üstelik bu güçlükler, ülkelerin geçişlerini etkileyebilecek, tarihsel geçmiş, gelişmişlik düzeyi, kültürel ve sosyo-ekonomik yönler açısından farklılık gösterebilir. Buna ek olarak, OHADA ülkelerinde IFRS'in yeni benimsenmesine ilişkin çalışma eksikliği göz önüne alındığında, bu makale geçiş süreciyle ilgili literatürdeki boşluğun doldurulmasına katkıda bulunacaktır. Ayrıca, geçiş sürecinin erken aşamalarında olan ülkelere bazı yanlış adımlardan kaçınmalarına ve diğerlerinin deneyimlerinden öğrenerek, Türkiye'de olduğu gibi tamamen IFRS uyumlu bir muhasebe sistemine başarılı bir geçiş için daha iyi hazırlanmalarına yardımcı olacaktır.
Keywords: Accounting standards; Approche comparée; Comparison; Comptabilité; International Accounting Standards; Local Accounting Standard

Cryptocurrencies in an insolvent estate - Du Plessis, Shandi (University of Johannesburg, 2021)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Smart contracts : the Fourth Industrial Revolution and private international law - Dwamena, Elizabeth (University of Johannesburg, 2021)
Please refer to full text to view abstract. LL.M. (International Commercial Law)

The Contents of the Articles of Association as a Document used in the Creation of Companies in Cameroon under the OHADA Law - Eposi, Gladys Nku Tiku (International Journal of Science and Research, 2021)
This study unveils that the creation of companies in Cameroon is been regulated by the OHADA[1], law under the Uniform Act on Commercial Companies and Economic Interest Groups (UACCEIG) which says, every company must have its own Articles of Association [2]. The Articles of Association is a document that contains the internal regulation for the management of the company’s affairs. [3] The articles of association are the contracts between the shareholders and the company and among the shareholders themselves. [4] The questions raised are what are the requirements common in the Articles of Association of all companies under OHADA Law? What effect do the AOA has? The study adopted an analytical approach which has led to the finding that the AOA under OHADA, is similar to the MOA [5] in most English speaking countries, but a major difference in that UACCEIG has limited the life span of the company to 99years while under English company law, a company goes on for an indefinite period. [6] The life span of the company should not be limited due to the principle of perpetual succession. The UACC seem to have concurred with some aspects of the Common Law, making the UACC an applaudable law reform.
Keywords: Articles of association; Cameroon; Commercial companies; Notarised deed; OHADA Law

Experimenting with international commercial dispute resolution - Erie, Matthew S; Bookman, Pamela K (AJIL Unbound, 2021)
In this essay, we describe the overlapping phenomena of new legal hubs (NLHs), international commercial courts, and arbitral courts. We survey their impact on the law and geopolitics of international commercial dispute resolution, identifying key issues these new dispute resolution institutions raise. While the rise of international commercial courts spans authoritarian and liberal states, Western and Asian states, common law and civil law traditions, it also highlights and builds upon regional differences. We question the assumption that the establishment of new courts is always consistent with an increase in the rule of law, particularly in non-democratic states. We close with thoughts about the potential influence and future role of these institutions. Some of the procedural innovations discussed here may lead to shifts in international commercial dispute resolution for years to come, but the question of whether there is sufficient demand for these new institutions lingers.

Corporate social responsibility and management of oil related conflict in Host Communities of Niger Delta Region, Nigeria - Gbali, Kenneth Chisom; Weli, Vincent Ezikornwor; Mmom, Prince Chinedu (World Journal of Advanced Research and Reviews, 2021)
The study sought to examine the Corporate Social (CSR) and management of oil related conflicts in Host Communities of the Southern States. Corporate Social Responsibility is the commitment of businesses to contribute to sustainable economic development by working with employees, the local community and the society at large to improve their lives in ways that are good for business and for development. The study was guided by three research objectives, three research questions and three hypotheses. The design adopted for this study is exploratory and descriptive research design and was conducted in Bayelsa, Delta and Rivers State in Nigeria. The population of this study comprised of 15,245,247 residents in Bayelsa, Delta and Rivers State in Nigeria. The instrument for data collection was a set of structured questionnaire. Data derived from the field were analyzed using the Statistical Package for Social Sciences (SPSS) version 23.0. And statistical tools such as mean and standard deviation were used to respond to the research questions, while inferential statistical tool of independent sample T-test was used to test the hypotheses at 0.05 level of significance. Findings from the study showed that there is a significant difference in the mean ratings of male and female respondents on the level of relationship between IOC’s and hosts Communities in Niger Delta Region, Nigeria ((P=0.738>0.05), df (400) =. -0.49273, p=0.738); there is a significant difference in the mean ratings of male and female respondents on the on CSR programs carried out by IOCs in hosts Communities in Southern Nigeria (P=.117>0.05), df (400) = -401.618, p=.117); further findings showed that there is a significant difference in the mean ratings of male and female respondents on the Factors causing conflict between oil companies and host communities in Southern, Nigeria (P=0.775>0.05), df (400) =382.256 p=0.775). Based on the findings of the study, it was recommended that host communities should be integrated into the planning process, a paradigm shift from planning for to planning with the host Communities, amongst others.
Keywords: CSR; Corporate Social Responsibility; Host communities; Oil Related Conflict; Oil companies; Southern Nigeria

COVID-19 and Comparative Corporate Governance - Gelter, Martin; Puaschunder, Julia M. (The Journal of Corporation Law, 2021)
With the pandemic caused by the novel coronavirus SARS-CoV-2 raging around the world, many countries’ economies are at a crucial juncture. The COVID-19 external shock to the economy has the potential to affect corporate governance profoundly. This Article explores its possible impact on comparative corporate governance. For an economy to operate successfully, a society must first find a politically sustainable social equilibrium. In many countries, historical crises—such as the Great Depression and World War II—have resulted in a reconfiguration of corporate governance institutions that set the course for generations. While it is not yet clear whether COVID-19 will have a similar effect, it is possible that it will change patterns of what kind of firms are -from an evolutionary perspective- likely to survive, and which ones are not. We argue that to some extent, it will accelerate ongoing trends, whereas in other areas it put corporations on an entirely new course. We observe three trends, namely the need for resilience, a growth of nationalist policies in corporate law, and an increasing orientation toward “stakeholder” interests. First, firms will have to become resilient to the crisis and consequently long-term oriented. Corporations that are not operating merely on an arm’s length capital market basis but are integrated into a network, generated by core shareholders, state ownership, or bank lending may be more likely to survive. In addition, firms are beginning to interact with their workforce differently in their attempts to maintain what could be called “healthy human capital.” Second, we are likely to see a resurgence of nationalism in corporate governance to ensure that foreign ownership and interconnected supply chains do not put national security at risk. Third, the existing critiques of inequality but also climate change awareness will accelerate the trend toward a broadening of corporate purpose toward “stakeholderism” and public policy issues. As in the past years, institutional investors acting as “universal owners” will play a role in shaping this trend.
Keywords: Behavioral; COVID-19; Climate change; Corporate governance; Corporate law; Economic protectionism; Evolutionary theory; Free cash flow; Green New Deal; Human capital; Inequality; Nationalism; Ownership structure; Relational finance; Shareholder primacy; Stakeholder theory; Varieties of capitalism

Corporate Finance - Gherghina, Ştefan Cristian (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book comprises 19 papers published in the Special Issue entitled “Corporate Finance”, focused on capital structure (Kedzior et al., 2020; Ntoung et al., 2020; Vintilă et al., 2019), dividend policy (Dragotă and Delcea, 2019; Pinto and Rastogi, 2019) and open-market share repurchase announcements (Ding et al., 2020), risk management (Chen et al., 2020; Nguyen Thanh, 2019; Štefko et al., 2020), financial reporting (Fossung et al., 2020), corporate brand and innovation (Barros et al., 2020; Błach et al., 2020), and corporate governance (Aluchna and Kuszewski, 2020; Dragotă et al.,2020; Gruszczyński, 2020; Kjærland et al., 2020; Koji et al., 2020; Lukason and Camacho-Miñano, 2020; Rashid Khan et al., 2020). It covers a broad range of companies worldwide (Cameroon, China, Estonia, India, Japan, Norway, Poland, Romania, Slovakia, Spain, United States, Vietnam), as well as various industries (heat supply, high-tech, manufacturing).

The impact of Covid-19 on labour law protection for Uber drivers - Gxabu, Mampho Aphelele (University of Johannesburg, 2021)
On 15 March 2020 the President of the Republic of South Africa announced a nationwide lockdown. The unpredicted pandemic dictated that extraordinary measures be put in place, which resulted in the country coming to a total standstill. Consequently, there was an alarming decline in economic activities and therefore government had to introduce measures to mitigate the impact of COVID-19 on employers and workers.

The Power of an Arbitral Tribunal to Determine Its Own Jurisdiction in International Commercial Arbitration - Kamanga, Patricia N. S. (Beijing Law Review, 2021)
Keywords: Arbitration Agreement; Competence-Competence; Jurisdiction; Party Autonomy; Power

The tax implications of intellectual property: an overview of the development of the law pertaining to deductions - Khan, Ilhaam (University of KwaZulu-Natal, 2021)
No abstract available.

Global Civil Procedure - King, Alyssa S. (SSRN Electronic Journal, 2021)
A “global” civil procedure has emerged and found its way into debates over procedural reform in both international and domestic arenas. Global civil procedure includes the procedural rules, practices, and social understandings that govern transnational litigation and arbitration. A global civil procedure norm is a norm adopted across courts or arbitration providers with the purpose of making that jurisdiction or provider more competitive in attracting transnational litigation or arbitration. Global civil procedure norms are at stake in multiple present trends and debates, including model laws in commercial arbitration, the procedure of international tribunals, the debate over investment dispute resolution, the rise of courts oriented towards international litigation, and sprawling litigation spanning multiple jurisdictions and fora. On a surface level, the values reflected in global civil procedure seem to be roughly the same across jurisdictions. A common language has emerged around competition for litigation business and procedure values such as efficiency, certainty, and impartiality. Yet different legal systems do not necessarily agree on the purpose of various shared elements of global civil procedure. For democracies, for instance, the purpose of procedural reforms might be to facilitate access to justice. Other countries may favor the same reforms because they facilitate top-down administrative control of judges. Surface agreement can submerge divergent logics that may ultimately lead to very different applications of harmonized rules. This Article begins by introducing the concept of global civil procedure, who uses it, and how. Next, it considers several examples of the phenomenon including conflicts of interest rules for adjudicators, aggrega tion, and discovery or disclosure rules. Finally, it considers the limits of global civil procedure. Although the rhetoric of procedural competition can be heard across systems, procedural values do not necessarily translate both in terms of enduring divisions between legal traditions and in terms of applications by current political regimes.

The conflict of jurisdiction between intra-EU BITs and European law: proposal for an EU investment court - Lewis, Krystle (Canterbury Christ Church University, 2021)
This work aims to find a practical solution to the problem that exists between intra-EU Bilateral Investment Treaties (BITs) and European Union (EU) law over conflict of jurisdiction issues. Currently, there is a problem as the EU Commission has rendered intra-EU BITs incompatible with EU law. This work argues that the current conflict of jurisdictional problems within investment agreements can be overcome by the creation of an EU investment court. The reliance on this court for the resolution of this conflict, as opposed to private law mechanisms, is important as it is the way forward in handling the conflict of jurisdiction issue at its best. This work argues that an EU investment court will be a panacea to the current problems concerning the conflict of jurisdiction. These problems will be presented through a positivist method where the law is analysed in its current form, highlighting its current weaknesses and resolving these weaknesses by proposing recommendations for such a court through a comparative examination of other international courts that fulfil a similar dispute resolution function, namely the Organisation for the Harmonisation of Business Law in Africa (OHADA) and the Unified Patent Court (UPC) and the World Trade Organisation (WTO). The purpose of this work is manifold. The work will provide an analytical examination of the relationship between EU law and international obligations within intra-EU BITs. It will further explore and assess the viability of a range of alternative solutions to intra EU BITs enforcement within the EU. It will additionally examine the operation of the OHADA, the UPC and the WTO to inform the proposal of an EU investment court. This is important as the outcome of these examinations will support the argument made in this thesis. It will also impact dispute resolution beyond academia by providing a practical solution to alleviate the current challenges with intra-EU BITs. The recommendations thus can inform changes for lex ferenda.
Keywords: Bilateral Investment Treaties (BITs); Investissements; Investments

The job security of employees of financially distressed companies - Loubser, Mieka E.; Garbers, Christoph (South African Mercantile Law Journal, 2021)
This contribution considers the legislative regulation of the job security (which boils down to preservation of employment) of employees in case of financial distress of a company. It juxtaposes the legislative regulation of four interrelated processes a company may engage in where it finds itself in financial distress, namely a voluntary internal restructuring (especially retrenchment), the transfer of the business or part of the business, business rescue and winding up. The legislative endeavour to preserve the job security of employees in all these processes is described and analysed. The discussion shows that room exists for companies to circumvent this protection and, to the extent that the protection does apply, that it remains difficult for employees to ultimately challenge the substance of decisions negatively affecting their job security. The main protection for employees in all these processes is procedural in nature and to be found in their rights to be informed of and consulted prior to decisions negatively affecting them. In this regard, business rescue is the most employee-friendly process. Participation in this process by employees, however, requires a fine balance as it may be self-defeating and lead to winding up and the permanent loss of jobs.
Keywords: Business rescue; Dismissal; Insolvency; Job security; Labor laws and legislation; Liquidation; Merger; Operational requirements; Retrenchments; Transfer of a business

The tripartite free trade area: towards a comprehensive African economic community with a particular focus on SADC - Mabinza, Siqhamo (University of KwaZulu-Natal, 2021)
No abstract available.
Keywords: Africa; GATT; Multilateral trading systems; Regional Trade Agreements (RTAs); SADC; Southern African Development Community; WTO

COFOLA International 2021: International and National Arbitration: Challenges and Trends of the Present and Future (Publications of the Masaryk University, theoretical series, editions Scientia, 2021)
- Virtual Arbitration Hearings in Times of COVID-19 (And Beyond); - International Arbitration and Blockchain: Current State, Types, Characteristics and the Future Perspective; - Use of Artificial Intelligence in Arbitration; - The Impact of Brexit on the Arbitration Procedure in Great Britain; - May Misapplication of EU Law Give Rise to International Responsibility of the Member State ... Under Investment Treaties? - International Investment Court System: The Future of Investment Dispute Settlement? - EU and Its New Mechanism for the ISDS in the Protection of FDI – What the Future Holds? - (Un)Clean Hands in International Investment Arbitration: Some Cleaning Required? - Challenges of Arbitrators in Inter-State Cases: A Different Cattle of Fish? - “Rules of Law” and Lex Mercatoria Determination Under the Auspice of ICC Arbitration; - Sources of Transnational Public Policy in International Commercial Arbitration; - Regulation of Arbitration Agreements Under New York Convention; - Comfortable Satisfaction Before the Court of Arbitration for Sport: Consistency Despite Differences? - Comparison of ICC Expert Report vs. ICC Arbitration Award; - Analysis of Civil Law Consequences of Corruption Under the Czech Law... in the Light of International Commercial Arbitration; - The Crime of Bending the Law From the Point of View of the Arbitrator ... of the Court of Arbitration and Application Practice; - The Arbitration Convention as One of the Measures to Eliminate Double Taxation ... in the European Union and in Slovak Republic; - Possibility of Resolving Individual Labor Disputes in Croatian Law by Arbitration; - What We Know, We Don’t Know About Macao’s Arbitration Framework and the Way Forward.

The principle of party autonomy in the HAGUE principles on choice of law in International Commercial Contracts : lessons for Chinese, Russian and South African Private International Law - Manganye, Makhanani Annastesia (University of Johannesburg, 2021)
It is no secret that there has been an increase in international trade in recent decades. Natural and juristic persons have taken it upon themselves to trade both domestically and internationally. As international trade increases so too do the conclusion of international commercial contracts. When individuals enter into an international contract, one particularly important issue, and one that should be foremost in the minds of the contracting parties, is which legal system will govern their agreement? Therefore, a significant factor to any international commercial contract is whether the parties have the freedom to choose the law applicable to their agreement and to choose the court that will adjudicate upon their contractual disputes, and if so, to what extent may the parties exercise their freedom of choice?... LL.M. (International Commercial Law)
Keywords: Commercial policy; Commercial treaties; International trade

Optimising the legal regulation of circular labour migration between South Africa, Lesotho and Zimbabwe - Matete, P. (North-West University, 2021)
Circular labour migration is steadily gaining prominence the world over, primarily due to the benefits it offers to the migrants, to the sending country, and to the receiving country – the so-called "triple-win" benefits. In order to enhance the benefits of circular labour migration, both the International Labour Organisation and the International Organisation for Migration recommend that adequate instruments of governance should be utilised. From the outset, this thesis recognises bilateral labour arrangements as the ideal instruments for enhancing the potential benefits that circular labour migration offers to the stakeholders involved in the process. As far as could be established, there has been no comprehensive research that seeks to provide insights on how the selected countries in the Southern Africa Development Community (South Africa, Lesotho and Zimbabwe) could optimise the benefits of circular labour migration for all stakeholders, primarily through the use of bilateral labour arrangements. The need for these insights in Southern Africa is pertinent due to the absence of a contemporary and clear framework regulating circular labour migration in the region. Based on the foregoing, this thesis advances the proposition that the guidelines provided by international law and standards of labour migration, and the best practices in Spain and New Zealand, can provide significant insights on how South Africa, Lesotho and Zimbabwe can enhance the regulation of circular labour migration to provide optimised benefits for all stakeholders. Proceeding from the above premise, this thesis makes a number of findings. These include the affirmation that bilateral labour arrangements are indeed the key regulatory instruments for promoting the triple-win benefits that circular labour migration offers; that circular labour migration, if managed well, plays an instrumental role in development in both the sending countries and the receiving countries; and that three key areas should be addressed in bilateral labour arrangements in order to effectively promote triple-win benefits. The three key areas that need to be addressed in bilateral labour arrangements in order to enhance the benefits for all stakeholders are linking migration with development, migration governance, and the protection of the rights of migrant workers. This thesis outlines the various principles that are necessary to give effect to these three key areas. This thesis finds that, based on the guidelines provided by international law and standards, it is essential that bilateral labour arrangements, at the minimum, incorporate provisions that facilitate skills training, the return and reintegration of migrants, the transfer of remittances, and the promotion of human resources development. In this regard, this study finds that the bilateral labour arrangements between South Africa and its neighbours, Lesotho and Zimbabwe, fall short of the guidelines provided by international law and standards on labour migration and by the best practices in New Zealand and Spain. The original contribution of this study lies in it being the first study to comprehensively explore the legal measures that South Africa, Lesotho and Zimbabwe could utilise to optimise the regulation of circular labour migration to South Africa as the main receiving country in SADC. This study makes recommendations on how the labour migration legal framework between the three countries can be improved, based on lessons learned from international law and standards on labour migration and best practices from selected countries.
Keywords: Bilateral arrangements; Circular labour migration; Droit du travail; Labour law; Migrant workers; Remittances; Travailleur migrant

Challenges for Responsible Investment in the retirement benefits sector of Kenya - Mathenge, Elizabeth (Victoria University of Wellington, 2021)
Responsible investment (RI) is the investment strategy that incorporates environmental, social and governance (ESG) factors into the investment decision-making process (Hebb, Hawley, Hoepner, Neher, & Wood, 2015). RI has shifted from what was considered a niche market to become one of the fastest-growing areas of finance in many parts of the world (PRI, 2019b). However, a closer look at the development of RI and adoption rates in countries and regions reveals that RI is not commonly practised in sub-Sahara Africa (except for South Africa). This study explores the critical challenges for RI development in the retirement benefits sector of Kenya and, by engaging with a variety of key stakeholders, proposes how to overcome the identified challenges. It contributes to the literature on challenges for RI in a developing country by offering an in-depth case study of the retirement benefits sector.My study employs qualitative methods to collect and analyse data collected from semi-structured interviews with 22 participants (asset managers, regulators and capital market experts, and a council member of the Association of Retirement Benefits Schemes of Kenya) as well as a collection of published documents by government agencies in Kenya. Also, I analysed 10 annual reports to assess the kind of ESG information that is disclosed by listed companies. My study explores, in particular, how actors in the retirement benefits sector conceptualise RI. It identifies the leading ESG factors in Kenya and draws on the business-case approach to RI to explore whether the participants consider those factors as material risk factors that present both risks and opportunities to the investment decision-making process. Further, my study identifies the specific barriers for RI development and proposes how to overcome them. The findings show that participants define RI using several terminologies. This is consistent with the existing literature. My study finds that all participants consider corporate governance as a material risk factor that can impact the financial returns of a portfolio. However, most of the asset managers do not think that the environmental and social factors can present material risk factors to their investment decision-making process. Although over a third of the asset managers recognise that the environmental and social issues in Kenya present business opportunities to retirement benefits schemes, there is a shortage of well-structured assets in those areas. Further, this study identifies five specific barriers for RI development: diversification challenges; a lack of ESG data; a lack of demand/incentives; short-termism; and the demand for high financial returns and a lack of awareness and expert knowledge of RI practices. My study recommends that the National Treasury of Kenya develops RI policy for the entire finance sector. In addition, the findings support a recommendation for the Capital Markets Authority and the Retirement Benefits Authority to embark on capacity building programmes to educate the actors in the finance sector on RI strategies and to create awareness of the impact of ESG on financial returns in the long run.
Keywords: Investment and Risk Management; Kenya; Responsible investment; Retirement benefits schemes

Governance of non-bank systematically important financial institutions - Morbee, Katrien (University of Oxford, 2021)
This thesis identifies the circumstances under which corporate governance regulation can help gain traction to minimise systemic risk. Systemic risk is the risk that local losses spread through the financial system and badly affect the financial system and the real economy. Excessive risk-taking by financial institutions can contribute to such systemic risk. Prudential regulation and supervision of financial institutions leave corporate decision-makers with room for discretion to increase or decrease systemic risk. The incentives of these decision-makers are not necessarily aligned with minimising systemic risk. The thesis shows that this problem exists across different business models. More specifically, it identifies perverse incentives in the case of systemically important banks, CCPs, mutual funds, and hedge funds. The need for corporate governance regulation therefore lies in the inherent incompleteness of prudential regulation and supervision. Corporate governance regulation can help fill this gap by regulating the environment within which choices are made within these types of institutions. The analysis has three steps. First, it characterises the systemic importance of financial-sector activities carried on outside the context of ‘banks’. The governance literature so far has focused on the ‘systemic externalities’ created by banks. However, our analysis shows that other non-bank SIFIs generate similar systemic externalities with socially harmful consequences. These systemic externalities are not considered by SIFIs when taking business decisions. In a second step, the thesis shows that prudential regulation and supervision are incomplete and leave room for governance regulation to fill in the gaps. The final step shows that a corporate governance framework focused solely on the interests of shareholders will have negative consequences for systemic stability. Given such divergence between the decision-makers’ and society’s interests, corporate governance regulation can complement the traditional prudential framework.
Keywords: Asset managers; Central counterparties; Corporate governance; Finance; Non-bank financial institutions; Systemic risk

The impact of the Trade-Related Aspects of Intellectual Property Rights (TRIPS) on the right to health and the right to development: a study of the implementation of TRIPS in Zimbabwe - Munemo, Ropafadzo Blessing (University of KwaZulu-Natal, 2021)
The right to health and the right to development are intertwined socio-economic rights that affect the well being and growth of a country’s populace. Most developing and least developed countries face challenges in ensuring access to essential medicines vis a vis the realisation of the right to health and full potential of development. Patents, provided for under the TRIPS Agreement are partly to blame for the lack of access to essential medicines as they account for the excessive pricing of medicines. Zimbabwe being a developing country currently facing dire economic and political challenges but being obliged under the International and Regional Human Rights Conventions it subscribed to, has to ensure the progressive realisation of the right to health and development. However, as a member of the TRIPS Agreement, there are limitations to the country’s ability to ensure access to medicines and healthcare for developmental purposes. This thesis has outlined the problematic provisions of the TRIPS Agreement and Zimbabwe’s attempt to use the flexibilities provided to its advantage. Zimbabwe has only put into use the flexibility of compulsory licensing and parallel importation to a limited extent; hence the recommendation that even though the country has domesticated the Agreement to its advantage, the country needs to explore other flexibilities comprehensively and promote the realisation of the rights to health and development.
Keywords: Access to medicine; Health care costs; Intellectual property; Public health; TRIPs; Trade tariffs; Zimbabwe

An analysis of the consequences of a business rescue moratorium on legal proceedings on property owners - Ngubane, Samukelo Siyanda (University of KwaZulu-Natal, 2021)
It has been over a decade since the Companies Act 71 of 2008 introduced business rescue proceedings which provided for the rescue of financially distressed companies. This procedure replaced the then statutory procedure of judicial management under Companies Act 61 of 1973. The business rescue proceedings begin with the general moratorium or stay on legal proceedings against the company or its property. This has a consequence that any claims against the company may only be enforced with the consent of the business rescue practitioner or the leave of the court. However, the courts continue to grapple with the interpretation, effect, and application of the key elements of business rescue provisions while always striving to accord respect to the legislative intention of business rescue as set out in section 7(k) of the Companies Act 71 of 2008. After a decade since its introduction, it is an opportune time to ascertain whether the business rescue proceedings is an effective corporate rescue procedure suitable to the modern-day demands of the South African economy. The research analyses the effect and the consequences of the moratorium on the rights of property owners. The moratorium has the effect that companies are given temporary immunity to actions brought by creditors which would have been due and enforceable. In this regard, the property leased by the property owner remains occupied by the company during business rescue proceedings as the property owner is barred by the moratorium to institute legal proceedings against the company. Further, when the repossession of the property is not possible and the rental due or installment is not payable by the company, the business rescue proceedings encroaches on the right of the property owners. The purpose of the research is to highlight the effect of the moratorium on the lease agreement between the company and property owners and the possible protection of the property owners’ rights. The study includes a critical analysis of judicial decisions on the moratorium, together with a discussion of the legal position in comparable foreign jurisdictions. In my conclusion, based on the findings, the business rescue is not free from imperfection. Therefore, I recommended that the legislature amend some parts of Chapter 6 of the Companies Act 71 of 2008.
Keywords: Companies Act 71 of 2008; Corporate rescue procedure; Financially distressed companies; South Africa; Stay on legal proceedings

Regulatory measures to address bank failures in Zimbabwe - Nyaude, Ashley Batsirai (University of Pretoria, 2021)
The main rationale of prudential bank regulation and supervision of banks has traditionally been to ensure the safety and soundness of banks and protection of depositors. However, best practice standards in bank supervision acknowledge that it is impossible to completely prevent bank failures. Therefore, it is crucial to have regulatory measures in place to deal with banks that fail. Banks are core players in the financial system as the intermediaries between savers and users of capital. In addition, banks provide critical services to consumers, small and medium-sized businesses, large corporate entities and governments who rely on them to conduct their daily business, both at domestic and international level. Banks also fulfil a sui generis role that sets them apart from other financial institutions that are role players in the financial system because, inter alia, they hold “highly” liquid liabilities in the form of deposits that are repayable on demand; they extend long-term loans that may be difficult to sell or borrow against on short notice; they are the back-up source of liquidity to all other institutions (financial and non-financial); and, are also the transmission belt for monetary policy. Unlike other players in the financial system, banks are vulnerable to loss of public confidence and to liquidity risk. Liquidity risk being the risk that a bank will not have sufficient cash to meet short term obligations and the fact that a "run on the bank" by depositors can result in devastating liquidity drainage. Because banks play a special role in the economy and their failure may have a significant impact on financial stability, they need a special approach when they become insolvent or are likely to become insolvent. The 2008 Global Financial Crisis (“GFC”) demonstrated the importance of special resolution regimes for banks; and the need to balance the interests of shareholders, creditors and depositors, while promoting financial stability objectives. Given the critical role of banks in the economy the need is clear for a special resolution regime for banks that provides a legal framework for regulators that avails to them a suite of resolution tools which they can apply to resolve the bank in an orderly manner; to rescue those parts of the bank that may still be viable and to liquidate those parts that are not whilst avoiding a drain on public funds. In order to deal with bank failures in Zimbabwe, the Banking Act [Chapter 24:20] has provided for the mechanism of curatorship since 2000, as a rescue measure aimed at restoring failing banks to economic viability. Curatorship has over the years been applied with mixed success; consequently, Zimbabwe has undertaken a number of reforms which include the enactment of the Troubled Financial Institutions (Resolution) Act in 2005; and the introduction of the problem bank regime via the Banking Amendment Act of 2015. Throughout these reforms, Zimbabwe has elected to retain curatorship, which was once a standalone process in banking legislation to enable bank rescue; and assimilated it into a broader bank resolution framework. This study seeks to determine whether Zimbabwe’s resolution regime requires to be strengthened and if so, to recommend reforms that will align the resolution regime in Zimbabwe with international best practice. For such purpose it will draw upon the Financial Stability Board’s Key Attributes of Effective Resolution Regime as international best practice benchmark. It will further also consider guidance yielded by a comparative study of the resolution regimes in the United Kingdom and South Africa.
Keywords: Bank failure; Bank supervision; Zimbabwe

A Third World approach to the role of South Africa, Nigeria and Kenya in the multilateral trading system - Nzimande, Nosiphiwo (University of KwaZulu-Natal, 2021)
No abstract provided.
Keywords: GATT; General Agreement on Trade and Tariffs; International Trade; Kenya; Nigeria; Regional Trade Agreements (RTAs); South Africa; WTO; World Trade Organization; World trade

Allocating rights between nations: Legitimacy and justice in international tax policy - Ozawa Ozai, Ivan (McGill University, 2021)
Although extreme poverty has decreased in the last decades, we are a long way from eradicating global poverty. Similarly, the world has seen a considerable decrease in global inequality due to recent developments in emerging economies, but overall inequality between nations has risen in the last decades. International tax law may have a relevant role in improving or worsening global inequality. Extensive research has shown that the present international tax system was designed in a way that tends to benefit high-income economies. However, there has been no significant discussion about whether and how international tax law rules should be changed to address global inequality. The main goal of this thesis is to analyze the existing legitimacy and distributive justice issues that limit the ability of lower-income countries to raise tax revenues and consider what can be done to make the current international tax regime more aligned with global justice principles.The thesis builds on the contemporary literature in international political economy and global distributive justice and puts forth a normative framework for allocating the international tax base among states. First, it analyzes some of the legitimacy deficits of the present international tax system. In contrast to prevailing views about improving legitimacy, it demonstrates the shortcomings of focusing solely on making international tax policymaking processes more inclusive and argues for a greater focus on global distributive justice. It then analyzes the main tax theories that have defined international tax relations to date and demonstrates some of their limitations. The final part of the thesis puts forth normative principles that integrate distributive justice and considers the practical implications of the proposed normative framework for some of the most recent issues discussed in international tax policy
Keywords: International tax; International tax policy

Sensitivity analysis of a bond mutual fund to yield curve - Pigou, Leuyou; Fono, Louis Aimé (Institut International des Assurances (IIA), 2021)

Takeover and shareholders' agreements - Sabatini, Federico (LUISS Guido Carli, 2021)
The OPA. Notions of takeover bids. Recognising and distinguishing the various forms of control within a company. Type of takeover bid. Subsequent defence techniques. The US control market and details of M&A and tender offers. Bids and acquisitions in China. Comparative European case studies. Shaldeholders' agreements. Regulatory sources and definition of covenants. Concerted action. Takeover obligations arising from concerted action. Cases. The Fondiaria-Sai case. Unipol-BNL. Other case of exemption.

Harmonization (or rather Standardization) of Cooperative Law in the OHADA Zone: What is the Result after Ten Years of Implementation of the Uniform Act? - Tadjudje, Willy (CIRIEC - España. Revista jurídica de economía social y cooperativa, 2021)
The Uniform Act related cooperative societies (UA-COOP) is the main source of cooperative law in all the seventeen States parties to the OHADA founding Treaty. Ten years after its entry into force (2011-2021), the aim of this study is to assess the level of enforcement of this Act. More concretely, the aim is to compare the state of cooperative law at the time of the entry into force of the UA-COOP (2011) with the current situation (in 2021). Such a comparison should make it possible to assess the contribution of the UA-COOP to the development of cooperative law and strengthening of national cooperative movements in the OHADA zone.

UNCITRAL Expedited Arbitration Rules - UNCITRAL (United Nations, 2021)

Chapter II: The Arbitrator and the Arbitration Procedure, An Arbitrator’s Imperative – How to Avoid Disappointing the Parties, Preventing Surprises and Enabling Efficient and Progressive Arbitral Proceedings - Welser, Irene; Mimnagh, Samuel (Austrian Yearbook on International Arbitration, 2021)

Improving international investment law’s treatment of (anti-)corruption: Towards a more balanced approach - Yan, Yueming (McGill University, 2021)
In recent years, investment arbitration tribunals are increasingly confronted with allegations of corruption, mostly invoked by host States as a defense to investors’ claims. After an affirmative finding of an alleged corrupt act between the investor and a public official of the host State in the establishment or conduct of the investment, tribunals have adopted a binary approach to the issue – if they uphold allegations of corruption, they completely dismiss the investor’s submissions. This binary approach has resulted in an asymmetry of liability for the two parties to a corrupt act (i.e., investors and host States/host State officials), failing to take into account the inherent bilateralism of corruption and the fact that domestic laws and international norms have outlawed both the act of offering and of accepting bribes. In particular, public officials’ free participation in a corrupt act to advance investments is attributable to the host State and requires State responsibility under international law. Moreover, the increasingly prevalent practice of inserting anti-corruption provisions in investment treaties has reinforced this lop-sided feature, as well as offering only weak effectiveness in terms of deterring corruption. After a careful examination of the treatment of corruption issues in investment arbitration and investment treaties, this thesis proposes a paradigm shift from the current asymmetric approach to a more balanced approach. It calls on investment tribunals to take a dual-track approach that investigates both corruption and investors’ claims, and ensures that each party assumes responsibility for its own misconduct. It also proposes that treaty drafters include anti-corruption provisions that impose strong obligations of anti-corruption on both sides of corruption (i.e., investors and host States) rather than merely on a single party to it
Keywords: Anti-Corruption Law; Investment arbitration; Investment treaty; Investments

Legalization through adjudication: The case of investor-state dispute settlement - Yu, Chen (McGill University, 2021)
The reform of the Investor-State Dispute Settlement (ISDS) mechanism has provoked much debate among legal scholars and practitioners. The critiques of ISDS mainly arise from concerns regarding the legitimacy of the mechanism such as the perceived tolerance for the lack of impartiality and consistency. To allay these concerns, there have been proposals to reform ISDS by establishing investment courts with tenured judges and appellate tribunals. However, international adjudication systems like ISDS cannot be fully analogized to domestic courts in common law countries: ISDS falls into a broader international regime where there are neither hierarchical/centralized decision-making and enforcement authorities nor a multilateral investment treaty, and the rules and principles on foreign investment protection are fragmented in around three thousand Bilateral Investment Treaties (BITs). Against this backdrop, this thesis argues that, although there is a general agreement among the international community to further legalize international investment law, the process of legalization via the specific avenue of reforming the adjudication mechanism (i.e. ISDS) is subject to (1) the institutional constraint of international investment law, especially the lack of shared understanding among the international community regarding the treatment of foreign investments, and (2) the internal constraints of adjudication as a mode of social ordering. It further cautions that pursuing predictability while disregarding the low level of shared understandings regarding investment protection may cause more legitimacy problems than it solves
Keywords: Bilateral Investment Treaties (BITs); ISDS Reform; International Investment Law; Investments; Investor-State Dispute Settlement